2001
DOI: 10.1038/sj.sc.3101103
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with sleep apnea in men with spinal cord injury: a population-based case-control study

Abstract: Objective: To characterize a population of spinal cord injury (SCI) patients with sleep apnea, and to determine associated factors and comorbidities Study Design: Population-based retrospective case-control study. Subjects: 584 male patients served by a Veterans Aairs SCI service. Measures: Medical records were reviewed for sleep apnea diagnosis, demographic information, neurologic characteristics, and treatments received. Sleep study reports were not available to determine the nature of abnormal respiratory e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
45
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(47 citation statements)
references
References 16 publications
1
45
1
Order By: Relevance
“…In patients with tetraplegia, apnoeas -especially the obstructive kind -have been found to be a significant problem (prevalence between 15 and 48%), interfering negatively with the quality of sleep. [26][27][28] Unfortunately, apnoeas cannot be verified by subjective reports. Apnoeas can be associated with, among other things, obesity (a high body-mass index) and the use of antispastic medication.…”
Section: Discussionmentioning
confidence: 99%
“…In patients with tetraplegia, apnoeas -especially the obstructive kind -have been found to be a significant problem (prevalence between 15 and 48%), interfering negatively with the quality of sleep. [26][27][28] Unfortunately, apnoeas cannot be verified by subjective reports. Apnoeas can be associated with, among other things, obesity (a high body-mass index) and the use of antispastic medication.…”
Section: Discussionmentioning
confidence: 99%
“…Case study reports suggest that compared with other individuals with similar levels of injury, obese individuals with SCI have more difficulties with transfers, have poorer functional outcomes, and require special equipment and additional staff time for transfers and personal care (33). Obesity in SCI has also been implicated in carpel tunnel syndrome, pulmonary embolism, and obstructive sleep apnea (34)(35)(36)(37)(38)(39). In people with SCI, obesity is commonly cited as one of the major risk factors for the higher prevalence of CVD in this population (40).…”
Section: Medical Consequencesmentioning
confidence: 99%
“…For example, the link between obesity and CVD risk factors and sleep apnea has been variable (48)(49)(50)(51). Akin to the general population, obesity may be a leading risk factor for sleep apnea in individuals with paraplegia, but it may not be strongest or the most common risk factor in individuals with tetraplegia (38). Because obesity predisposes individuals to sleep apnea by excessive fat deposition in the upper pharyngeal area, Burns and colleagues suggest that total body fat may be a better marker of sleep apnea in individuals with SCI (38).…”
Section: Medical Consequencesmentioning
confidence: 99%
See 1 more Smart Citation
“…Sleep apnea is often present after SCI, but the exact prevalence is not known. Burns et al reports sleep apnea in up to 40% of individuals with SCI (21,22). Flavell et al (23) diagnosed severe nocturnal hypoxic episodes in 3 of 10 individuals with tetraplegia, and Cahan et al (24) reported on 6 of 16 patients with tetraplegia who had normal oxygen saturations during the day and demonstrated desaturation at night.…”
Section: Discussionmentioning
confidence: 99%